A Day in the Life: A Daily Diary Examination of Marijuana Motives and Protective Behavioral Strategies Among College Student Marijuana Users. (April 2020) - Pearson, Matthew R.; Bravo, Adrian J.; Conner, Bradley T.; Parnes, Jamie E.
This study examined marijuana-use motives and protective behavioral strategies (PBS) as within- and between-subject predictors of marijuana-related outcomes. Furthermore, we explored differences between a specific marijuana-related event (i.e., 4/20) compared with typical weekend/weekday use. Forty-three college student marijuana users (31 females) completed daily surveys for 12 days (April 15–April 26, 2016). Four motives (coping, conformity, enhancement, and social) were associated with more negative consequences within-subjects. Enhancement and conformity motives were also associated with a higher number of use sessions, and expansion motives were associated with higher subjective high. Marijuana PBS use (total score) was associated with fewer sessions and lower subjective high within-subjects. Social motives were higher, whereas PBS use and coping motives were lower on 4/20 compared with other days. Our findings support PBS and certain use motives as promising intervention targets for college student marijuana users.